GAMBARAN STATUS GIZI KURANG BERAT BADAN KURANG DAN BERAT BADAN TIDAK NAIK PADA BALITA YANG DIBERIKAN MAKANAN TAMBAHAN BERBAHAN PANGAN LOKAL DI WILAYAH KERJA PUSKESMAS PUPUAN I - Evayanti, Ni Luh Gede (STIKES ADVAITA MEDIKA TABANAN, 2025)
Intoduction: Toddlers are the group most vulnerable to experiencing nutritional problems, especially malnutrition problems such as being thin, short and malnourished. The government is implementing a program for providing additional food made from local food, which is one of the strategies for dealing with nutritional problems for children under five. Methods: This research uses a quantitative design with an analytical observational design with a questionnaire and primary data sources. The research was carried out in October 2024 using total sampling. The sample size in this study was 36 respondents. Result: The research results found that the nutritional status of toddlers after receiving additional food made from local food was underweight in the category of two toddlers (5.6%). There were 15 (41.7%) toddlers with good nutritional status, while there were 19 (52.8%) toddlers with normal weight. The nutritional status of toddlers improved after being given additional food made from local ingredients due to the role of cadres in processing, supervising and providing education regarding the provision of local additional food so that mothers are able to prepare additional food, diligent toddlers to integrated service posts, democratic parenting. Suggestion: It is hoped that the Puskesmas nutrition program managers will continue the program of providing additional food made from local food to improve the nutritional status of children with problems Keywords: hemoglobin, body mass index, upper arm circumference, nutritional status. Keywords: Nutritional status; Additional Food Made from Local Food.